Pembuatan Kafein Benzoat Secara Semisintetis Dari Serbuk Teh Kayu Aro - Fitra Fauziah; Zulharmita Zulharmita; Wahyu Ningsih (STIFARM Padang, 2017)
Caffeine benzoate semisynthetis had been create from tea powder which produced by PTP Nusantara VI Kayu Aro, District of Kerinci, Province of Jambi. Caffeine was isolated from 25 grams of tea powder by fractionated and crystallized to obtained 102 mg of caffeine crystals. Caffeine crystals isolated as much as 50 mg was reacted with 32 mg of benzoic acid the result was 30 mg of caffeine benzoate. Caffeine benzoate was characterized which organoleptic form was fine powder, greenish-white color, bitter taste, and distinctive odor. Melting point was 196 oC. Infrared spectrum showed group O-H at wave number 2700-2500 cm-1, which it did not show on spectrum caffeine crystals. The maximum absorption wavelength was obtained 273.5 nm. Profile of thin-layer chromatography which stationary phase silika gel 60 F254 and mobile phase chloroform : ethanol (99:1) was obtained Rf value 0.35.